Efficacy of Selected Medicinal Plants of Kaya Kauma and Kaya Tsolokero Against Bacterial Diseases - Rajat, Jolly; Jefwa, Joyce Mnyazi; Mwafaida, Joseph Mghalu (European Journal of Applied Sciences, 2023)
An ethnobotanical study was carried out in the sacred Kaya forests of Kauma and Tsolokero in Kilifi County in Kenya. Ethnobotanical data on useful and medicinal plants was collected. Communities living around these two forests basically depend on the diversity of flora for their livelihoods. The local herbalists use indigenous trees and shrubs to treat a variety of diseases. These skills have been passed down through generations. In this study, a survey was carried out in twenty-six villages around Kaya Kauma (18) and Kaya Tsolokero (8). The population was interviewed for knowledge on medicinal plants. More emphasis was put on the Traditional herbal practitioners (THPs) possess more information on herbal plants, their preparation and prescription for ailments they reportedly treat. Preliminary reports indicated that most commonly treated ailments were caused by bacteria, fungi and viruses in that order. Based on this, Eleven (11) medicinal plants recommended for bacteria-related ailments were selected and tested in the laboratory to validate their efficacy against Escherichia coli and Staphylococcus aureus. Suspensions of S. aureus and E.coli were prepared form 24h fresh colonies and diluted to x10-7 cfu/ml where 100µl of each were plated to dry on 9cm plates filled with King B media. A protocol adopted from the THPs was used to prepare medicinal plant formulations from the selected plants. The plant materials were subjected to soaking, boiling or roasting as recommended and finally formulated in SDW at 1:1 (Wt/Vol). About 40µl of the plant formulations diluted at x10-1, x10-2 and x10-3 and SDW as control treatment were loaded on sterile paper plugs, allowed to air dry in a laminar flow before placing them equi-distantly at 4 cm radius on the inoculated King B media plates. More than (64%) of tested plants suppressed the growth of either S. aureus or E.coli while 4 (>30%) suppressed both test bacteria. In total, 91 medicinal plants were mentioned by communities in Kaya Kauma (48) and Tsolokero (43). THPs from the two forest commonly treated ailments caused by bacteria, fungi and viruses in that order. The bioassay tests in this study validated the potency of more than 75% of the recommended medicinal plants that treated bacterial infections. Concentrations used in the study were far below what is recommended by THPs which raises concerns of possibilities of over prescriptions. There is need therefore to regularize and standardize products from this fast-growing industry.